Maṣlaḥah-Based Legitimacy of Expanding Fī Sabīlillāh in Zakat: Yusuf al-Qaradhawi's Ijtihād in the Digital Age - Muhammad Akmalul Rizal; Muhammad Sidqi Abdurrahman; Rahmat Hidayat Rumdainis (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2026)
This article examines the ijtihād of Yusuf al-Qaradhawi in expanding the meaning of fī sabīlillāh as a category of zakat recipients through the framework of maqāṣid al-syarī‘ah, particularly the concept of maṣlaḥah. While previous studies have explored the methodological aspects of al-Qaradhawi’s expansion of jihād from military to intellectual, educational, social, economic, and political domains, its normative legitimacy in relation to the preservation of religion (ḥifẓ al-dīn) in the digital age remains underexplored. Employing qualitative library research with content analysis, this study finds that: (1) al-Qaradhawi’s ijtihād is firmly grounded in maṣlaḥah, particularly the notion of urgent necessity (al-maṣlaḥah al-mulḥiḥah) in responding to intellectual and cultural warfare (al-ghazw al-fikrī wa al-tsaqāfī); (2) the six categories of activities he legitimizes—da‘wah institutions, Islamic research centers, Islamic media, publications, cadre training, and support for persecuted preachers—directly contribute to ḥifẓ al-dīn; and (3) these activities, originally situated within maṣlaḥah ḥājiyyah, have evolved into ḍarūriyyah in the context of digital disruption. This study contributes to contemporary ijtihād discourse by demonstrating that contextual expansion of textual meanings can be normatively justified when aligned with higher objectives of the Sharī‘ah, particularly under conditions of epistemic contestation in digital environments.a